Media Support of University Activities in the Context of University Image Promotion - V. A. Pulkina; G. V. Korshunov (Высшее образование в России)
In modern market conditions universities have to interact with multiple and diverse groups of the public. To enhance competitiveness, universities are transforming communicationpolicies into specific target audiences and new channels of communication. Therefore, the media support of the university, the creation and maintenance of its positive image require more attention from the management. The strategic importance and practical implementation of the university’s communication policy and the development of partnerships with the external environment determine the urgency of these issues for higher education in Russia at the present stage of professional education development. On the example of Ukhta State Technical University the authors view thechannels and tools of University’s communication in the context of its image global promotion. The University media centre and the Office of strategic communications serve as a main informationsource. They inform the target audience by means of print media, TV news channel, University site, press release distribution, and social media. The other area of University’s communication policy issectoral media cooperation, participation in a special communicational project, which encompasses more than 60 universities and 90 industrial companies. The University also organizes special events that have different themes and scopes. The event marketing is an effective tool to boost its media image. The University positions itself as a socially oriented organization possessing the necessary infrastructure, professional and material resources for the development of business, science, sports, creativeinitiatives, volunteering within the scope not only city and region but also the whole country